Digital Learning as a Key Strategy for Enhancing Employee Competencies - Hidayat, Muhammad Iqbal; Rahmadani, Aulia Fitri (Universitas Sains dan Teknologi Komputer, 2026)
This study employs a quantitative, explanatory design using a survey administered to 180 employees who have participated in digital learning programs within the organization under investigation. The study population comprises all employees with direct experience in digital learning. A purposive sampling technique was applied based on the criteria of active employees who had engaged in digital learning at least once within the past six months and were involved in work activities requiring competency development, while interns and employees who had never participated in digital learning were excluded. The sample size of 180 respondents was considered adequate for quantitative analysis and linear regression testing and is consistent with the figures reported in the abstract, results, and discussion sections. Data were collected through a structured questionnaire employing a five-point Likert scale and analyzed using simple linear regression to examine the effect of digital learning on employee competency.